Global Citizenship: A Critical Reader - Nigel Dower; John Williams (Edinburgh Edinburgh University Press, 2011)
Global citizenship is a dynamic topic within the modern world. Emerging from the language and ideas that are being developed to try to encompass and define the ways in which globalization is changing the world in which we live, global citizenship combines two factors - the idea of global responsibility (for the environment, aiding the poor, human rights, peace, etc) and the development of institutional structures through which this responsibility can be exercised.
Keywords: Globalization; Textbooks; Global Citizenship (BIN1064-N)